Nonlinear relationship between hepatic steatosis index and reversion to normal glucose regulation in Chinese adults with prediabetes - Haiyong Zeng; Fei Yu; Haofei Hu; Yong Han; Ruixue Ye; Changchun Cao (Scientific Reports)
Abstract The hepatic steatosis index (HSI) has been demonstrated to have a significant correlation with prediabetes and diabetes; however, its potential association with reversion to normal glucose regulation (NGR) from prediabetes remains insufficiently investigated. The primary objective of this study was to elucidate the relationship between HSI levels and the probability of reversion to NGR among Chinese adults with prediabetes. This retrospective cohort study utilized health examination data from 11,241 Chinese adults with prediabetes. Cox proportional hazard models were employed to calculate hazard ratios (HR) and 95% confidence intervals (CI) to assess the association between HSI levels and reversion to NGR. Additionally, a Cox proportional hazards regression model incorporating cubic spline functions and smooth curve fitting was utilized to determine any nonlinear relationships between HSI levels and reversion to NGR. The results of the multivariate analyses demonstrated a significant association between reduced HSI levels and an increased likelihood of reversion to NGR (HR = 0.92, 95%CI: 0.89–0.95, P < 0.0001). Furthermore, a nonlinear relationship was identified between HSI levels and the reversion to NGR, with a critical threshold at an HSI value of 43.08. Below this threshold, a strong negative association was observed, markedly enhancing the probability of returning to normoglycemic status (HR = 0.91, 95% CI: 0.88–0.94, P < 0.0001). This study reveals a negative, nonlinear correlation between HSI levels and the reversion to NGR in individuals with prediabetes. These findings highlight the essential role of effectively managing HSI as part of comprehensive prediabetes treatment strategies, which may significantly enhance the likelihood of achieving normoglycemic status.